[Mn14] "Structural Analogues" of Well‐Known [Mn12] Single‐Molecule Magnets. Issue 35 (31st August 2018) - Charalambous, Maria; Moushi, Eleni E.; Nguyen, Tu N.; Mowson, Andrew M.; Christou, George; Tasiopoulos, Anastasios J.
Abstract : A new family of tetradecanuclear Mn clusters [Mn III 10 Mn IV 4 (µ3 ‐O)12 (EtCO2 )12 (pd)4 (EtOH)4 (py)4 ](ClO4 )2 (1 ), [Mn III 10 Mn IV 4 (µ3 ‐O)12 (EtCO2 )12 (mpd)4 (EtOH)2 (H2 O)2 (py)4 ](ClO4 )2 (2 ), and [Mn III 10 Mn IV 4 (µ3 ‐O)12 (MeCO2 )10 (pic)4 (pd)4 (pdH2 )4 ] [3 ] (picH = picolinic acid) were prepared from the use of the aliphatic diols 1, 3‐propanediol (pdH2 ) and 2‐methyl‐1, 3‐propanediol (mpdH2 ). The [Mn III 10 Mn IV 4 ] aggregates consist of a [Mn III 10 ] outer ring surrounding a [Mn IV 4 ] defective dicubane. Interestingly, the core of1 –3 is similar to those of a [Mn12 (µ3 ‐O)12 (RCO2 )16 (H2 O)4 ] "normal [Mn12 ]" and a modified [Mn12 ] aggregate consisting of a [Mn III 8 ] ring, surrounding a [Mn IV 4 ] defective dicubane called "flat [Mn12 ]". Dc and ac magnetic susceptibility studies revealed the presence of dominant antiferromagnetic exchange interactions in complexes1 –3 leading to small spin ground‐state values. Abstract : Three new tetradecanuclear Mn clusters were prepared from the use of the aliphatic diols 1, 3‐propanediol and 2‐methyl‐1, 3‐propanediol. They consist of a [Mn III 10 ] outer ring surrounding a [Mn IV 4 ] defective dicubane and exhibit a [Mn III 10 Mn IV 4 (µ3 ‐O)12 ] 22+ structural core that is similar to the Mn/O 2– cores of well‐known [Mn12 ] single‐molecule magnets.